Synthesis of Heteroarylogous 1H-Indole-3-carboxamidines via a Three-Component Interrupted Ugi Reaction - La Spisa, Fabio; Meneghetti, Fiorella; Pozzi, Beatrice; Tron, Gian Cesare (Synthesis, 2015)
A novel one-pot multicomponent synthesis of heteroarylogous 1H-indole-3-carboxamidines starting from readily available N-alkyl-N-(1H-indol-2-ylmethyl)amines, isocyanides, and carbonyl compounds is reported. The strategy exploits the ability of the indole nucleus to interrupt the classical Ugi reaction, by intercepting the nascent nitrilium ion.
Keywords: isocyanides; secondary amines; Ugi reaction; multicomponent reactions; indoles